Current Spreading Effects in Vertical GaN‐Based Light‐Emitting Diode on Si(111) Substrate. Issue 4 (1st July 2016) - Wei, Jingting; Zhang, Baijun; Wang, Gang
Abstract : The optimal design of GaN‐based Lightemitting diode (LED) is important for its reliability. In this work, a new three‐Dimensional (3D) circuit model with a resistor network is developed to study the current distribution in the active layer of vertical conducting GaNbased LED grown on Si(111) substrate with different structures and electrode patterns. It consists of resistance of Transparent conductive layer (TCL), resistance of epitaxial layer, intrinsic diodes presenting the active layer, and AlN/Si junction as which the multilayer of AlN/Si is assumed. Simulations results of current distribution in active layers of two kinds of LED structures show that current distribution uniformity is greatly affected by the electrode pattern and the LED structure. Furthermore, the experimentally measured light emission uniformity agrees well with simulation results. The electrical and optical characteristics of LED are obviously affected by the current distribution uniformity.